Letters of Edward FitzGerald, in Two Volumes. Vol. 2 - FitzGerald, Edward, 1809-1883; Wright, William Aldis, 1831-1914 (Salt Lake City, UT : Project Gutenberg, 2007)
"Letters of Edward FitzGerald, in Two Volumes. Vol. 2" by Edward FitzGerald is a collection of personal correspondence likely written in the mid-19th century. This volume presents the letters of FitzGerald, an esteemed translator and literary figure, exploring themes of friendship, literary pursuits, and reflections on life. It provides insight into the thoughts and relationships of FitzGerald, particularly his interactions with prominent contemporaries, including discussions of his translation work and personal losses. The opening of this second volume reveals FitzGerald's intimate correspondence with his friends, sharing news of his life, thoughts on literature, and the impact of sorrowful events, particularly the passing of his close friend William Browne. His letters showcase a blend of wit, melancholy, and a deep appreciation for literature, as he references translations and works of Persian poetry, particularly Omar Khayyám. FitzGerald's reflections on his solitude and the changing world around him resonate throughout these letters, creating a portrait of a man grappling with both personal grief and the passage of time, set against the backdrop of his literary endeavors. (This is an automatically generated summary.)
Release date is 2007-02-06
Transcribed from the 1901 Macmillan and Co. edition by David Price
Keywords: Authors, English -- 19th century -- Correspondence; FitzGerald, Edward, 1809-1883 -- Correspondence